Inventarisasi Potensi Desa Di Daerah Aliran Sungai (Kajian Di Desa Buluh Cina Kecamatan Siak Hulu) - Wan Asrida; Tiyas Tinov; Paulus Gia (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2011)
The inventory on Buluh Cina potency is conducted in the effors to make community developmentprogram. Data obtained from the inventory are highly important in making planning, thus the villageauthorities are able to carry out analysis and prediction on the future tendency. The data are also veryuseful for decision making to achieve prosperious society as mentioned by the nation goal. The maingoal of this research is to gather information on the used and un-explored village potency. The informationand data were obtained directly from village secretary, key persons and other souces in the village usingboth direct questions to key informant and from the documents available in the village office. The resultsfrom research locations indicate that the Buluh Cina village contains a wide variety of potencies such asits strategic location, fertile lands for agriculture, plantation and foresty, minerals, water potency in river fortransportation, fishery and hatchery, water potency in lake and swamp area, tourisms due to its tradition (Balimau Kasai, Tobo Bajambe, Pangean Martial Arts, Bediki Dabano, Calempong) and culture. However,the un-explored potency available in Buluh Cina includes KUD revitalization and biogas.